A shoppers' paradise : how the ladies of Chicago claimed power and pleasure in the new downtown - Remus, Emily, 1984- (Harvard University Press, 2019)
A Shoppers' Paradise examines the incorporation of women consumers into public space and public culture. The site is Chicago at the turn of the twentieth century--when the city, rising like a phoenix after the Great Fire, became a center of debate over capitalist urbanism. The book explores the new practices of public consumption that monied women pursued on the streets of the city's burgeoning retail district and in the restaurants, hotels, department stores, and theaters built by entrepreneurs who invited their patronage. It also brings to light the conflict evoked by ladies' public presence, as city officials, clergymen, and influential industrialists responded to their conspicuous new habits of consuming in an urban public sphere that had once been the preserve of men. At stake, the book demonstrates, were competing visions of urban commerce, the place of women, and the cultural legitimacy of new forms of consumption. These conflicts, over gender and space, shaped the creation of a built environment and cultural norms that upheld women's consumption and sustained the rise of American consumer capitalism.--